PENETAPAN KADAR FENOL TOTAL DAN KATEKIN DAUN TEH HITAM DAN EKSTRAK ASETON TEH HITAM DARI TANAMAN CAMELLIA SINENSIS VAR. ASSAMICA - N. L. P. V. Paramita; N. P. T. W. Andari; N. M. D. Andani; N. M. P. Susanti (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2020)
Indonesia is quite well known as one of the countries that has tea plantations and uses its own production of tea. As a tea producing country, Indonesia has been able as a tea exporter. The most tea production in Indonesia is black tea product. Black tea products are produced from species Camellia sinensis Var. Assamica which undergoes an enzymatic oxidation process to fresh tea leaves. The most phenolic compounds contained in the black tea leaf are catechins, theaflavins, and thearubigin. The purpose of this study was to determine the phenolic total and catechin content of black tea products and acetone extracts produced by D'wan Tea (DT) and Bali Cahaya Amertha (BCA) plantations which located in Tabanan district, Bali. Determination of total phenol was carried out on black tea leaf products and acetone extract using the Folin-Ciocalteu method compared with gallic acid standards. Determination of catechin content was performed on fresh (before oxidized) tea leaves, black tea leaf products, and acetone extracts using the UV-Vis Spectrophotometry method at a maximum wavelength of 257 nm. The results showed that total phenol content of D'wan Tea black tea products (SDT) and Bali Cahaya Amerta (SBCA) were 1.50 ± 0.02 % mg GAE/g dan 0.97 ± 0.02 % mg GAE/g, respectively. Results of the total phenol content of D'Awan Tea (EADT) black tea acetone extract was 6.92 ± 0.12 % mg GAE/g, while the Bali Cahaya Amerta (EABCA) black tea acetone extract was 7.38 ± 0.07 % mg GAE/g. Catechin content from fresh leaf samples of D'wan Tea (SSDT), SDT, and EADT were 15.30 ± 0.22 % mg/g, 8.37 ± 0.13 % mg/g, and 37.45 ± 0.74 % mg/g. Catechin content of fresh leaf samples of Bali Cahaya Amerta (SSBCA), SBCA, and EABCA were 14.71 ± 0.28 % mg/g, 15.16 ± 0.58 % mg/g, and 35.66 ± 0.89 % mg/g. Total phenol content of DT black tea products is greater than BCA black tea products. DT black tea products appear to have decreased catechins in processing. In the processing of black tea it is necessary to decrease catechins content due to the formation of catechin polymers, namely theaflavin and thearubigin as a determinant of the quality of black tea. Keywords: black tea, Camellia Sinensis, cathecin, total phenol.